More day in the night? The gentrification of London’s night-time through clubbing - Alessio Kolioulis (Bollettino della Società Geografica Italiana)
Since the 1990s, dance cultures played a key role in revitalizing post-industrial cities. As recent research indicates a correlation between the closure of music venues and gentrification processes, few studies explore how nightclubs are a central part of urban regeneration. The proposed article uses a governmentality framework to assess London’s 24-hour City Vision and the business model of a new mega-club, Printworks, funded by estate giant British Land, arguing that London’s attempt to ‘save nightlife’ requires a better understanding of the dynamic between the night-time economy and urban planning.